THE ROLE OF IMAM AL-BUKHARI’S "SAHIH" HADITHS IN IMPROVING PERSONAL SPIRITUALITY - Qalandarova, Farida Azamatovna (Innovative Development in Educational Activities, 2023)
The article reflects the declaration of Bukhara as the capital of Islamic culture, the interpretation of the hadiths of our prophet, the manifestation of the concept of love as a humanitarian feeling in the authentic hadiths of Imam al-Bukhari, the great leader of the Islamic world.